Analysis of the Use of Augmented Reality-Based Learning Media on Conceptual Understanding Ability - Syifa Urrahmah; Elfi Tasrif; Vera Irma Delianti; Lativa Mursyida (Universitas Negeri Padang, 2025)
In the era of technological advancement, education must continually innovate by utilizing effective learning media, such as augmented reality (AR). AR creates an interactive and engaging learning environment by combining real-world visualization with virtual objects, making it a focus in education to enhance conceptual understanding. This study aims to analyze the validity, practicality, and effectiveness of AR-based learning media in improving students' conceptual understanding of computer hardware materials in Informatics subjects. The research was conducted in classes X TKJ 1 and X TKJ 2 at SMK Negeri 5 Padang, using multiple-choice objective test instruments and questionnaires. The results indicate that the use of AR-based learning media has a significant impact on improving students' conceptual understanding. This is evidenced by the hypothesis test results showing a sig. (2-tailed) value of 0.00 (<0.05) and an N-gain score of 0.7293 (high category), with an effectiveness percentage of 72.92%. AR-based learning media was deemed highly feasible as supplementary learning media based on expert validation (95%), as well as practicality questionnaires from teachers (95%) and students (87%). The advantages of AR media include realistic visualization, the ability for repeated observation, a more interactive learning experience, and efficiency in the use of teaching aids. Thus, the implementation of AR in learning has proven effective in enhancing students’ conceptual understanding and providing a more engaging and meaningful learning experience.